New approaches to determine fatigue in elite athletes during intensified training: Resting metabolic rate and pacing profile - Woods, A. L.; Garvican-Lewis, L. A.; Lundy, B.; Rice, A. J.; Thompson, K. G. (PLOS ONE, 2017)
Background: Elite rowers complete a high volume of training across a number of modalities to prepare for competition, including periods of intensified load, which may lead to fatigue and short-term performance decrements. As yet, the influence of substantial fatigue on resting metabolic rate (RMR) and exercise regulation (pacing), and their subsequent utility as monitoring parameters, has not been explicitly investigated in elite endurance athletes. Method: Ten National-level rowers completed a four-week period of intensified training. RMR, body composition and energy intake were assessed PRE and POST the four-week period using indirect calorimetry, Dual-Energy X-Ray Densitometry (DXA), and three-day food diary, respectively. On-water rowing performance and pacing strategy was evaluated from 5 km time trials. Wellness was assessed weekly using the Multicomponent Training Distress Scale (MTDS). Results: Significant decreases in absolute (mean ± SD of difference, p-value: -466 ± 488 kJ.day-1, p = 0.01) and relative RMR (-8.0 ± 8.1 kJ.kg.FFM-1, p = 0.01) were observed. Significant reductions in body mass (-1.6 ± 1.3 kg, p = 0.003) and fat mass (-2.2 ± 1.2 kg, p = 0.0001) were detected, while energy intake was unchanged. On-water 5 km rowing performance worsened (p < 0.05) and an altered pacing strategy was evident. Fatigue and total mood disturbance significantly increased across the cycle (p < 0.05), and trends were observed for reduced vigour and increased sleep disturbance (p < 0.1). Conclusion: Four weeks of heavy training decreased RMR and body composition variables in elite rowers and induced substantial fatigue, likely related to an imbalance between energy intake and output. This study demonstrates that highly experienced athletes do not necessarily select the correct energy intake during periods of intensified training, and this can be assessed by reductions in RMR and body composition. The shortfall in energy availability likely affected recovery from training and altered 5 km time trial pacing strategy, resulting in reduced performance